Nursing of a patient with mastitis of Qi-stagnation and Heat-congestion type treated by manual lymphatic drainage of the breast combined with blood-pricking and cupping therapy (手法排乳联合刺络放血拔罐治疗1例气滞热壅型乳腺炎患者的护理) - LI Suna (李苏娜); LIU Kexin (刘可欣); CHEN Hong (陈宏) (Association of Integrative Nursing, 2022)
This paper summarized the curative effect of manual lymphatic drainage of the breast combined with blood-pricking and cupping therapy and related nursing measures for a patient with mastitis of Qi-stagnation and Heat-congestion type. The manual lymphatic drainage of the breast was carried out under the guidance of Traditional Chinese Medicine syndrome differentiation, and then combined with the selection of Dazhui point (DV 14) and Tianzong point(SI 11) for blood-pricking and cupping therapy, so as to achieve the effect of relieving symptoms and expression of breast milk. The manual lymphatic drainage of the breast combined with blood-pricking and cupping therapy, supplemented by symptomatic nursing, can effectively alleviate the symptoms of patients and improve the treatment effect. (本文总结手法排乳联合刺络放血拔罐技术治疗1例气滞热壅型乳腺炎患者的效果和护理措施。在中医辨证指导下进行手法排乳, 再配合选取大椎穴、天宗穴行刺络放血拔罐, 从而达到症状缓解、乳汁排出通畅的效果。手法排乳联合刺络放血拔罐治疗乳腺炎, 同时辅以对症护理, 能够有效缓解患者症状, 提高治疗效果。)